Leadership in innovation projects: An illustration of the reflective practitioner and the relation to organizational learning - Peter R. A. Oeij; Jeff B. R. Gaspersz; Tinka van Vuuren; Steven Dhondt (Journal of Innovation and Entrepreneurship, 2017)
The purpose of this conceptual article is to demonstrate that Donald Schön's Reflective Practitioner actually outlines an explicit model of the steps that project leaders in practice apply largely unaware. This reflective research model furthermore can be meaningfully combined with Argyris and Schön's model of organizational learning. The combined research and learning model can support project team members and leaders to enhance their reflectiveness and improve their project success. Eighteen project leaders of innovation teams were studied by means of in-depth interviews aimed at assessing how project leaders act when dealing with critical incidents during their projects. Based on a selection of three project leaders, an empirical illustration of Schön's model is provided: they recognized there was a problem, researched the problem, developed alternative solutions, tested different solutions and alternatives on validity, tried out and experimented with solutions, selected and applied a particular solution, and evaluated the process completed. The authors' suggestion for practitioners is applying the combined model of the reflective practitioner and organizational learning, as this can help innovation leadership in practice at both the individual and the team level. The scientific value of this contribution lies in the conversion of Schön's latent (tacit) model into a manifest (explicit) model, and by relating it to the model of organizational learning, a result emerges that is both applicable to future research and practice.
Keywords: 650; Reflective practitioner; Organizational learning; Project management; Innovation leadership